Approaches for Collaborative Security Defences in Multi Network Environments - Koning, Ralph; Polevoy, Gleb; Meijer, Lydia; de Laat, Cees; Grosso, Paola (2019 6th IEEE International Conference on Cyber Security and Cloud Computing (CSCloud)/ 2019 5th IEEE International Conference on Edge Computing and Scalable Cloud (EdgeCom))
Resolving distributed attacks benefits from collaboration between networks. We present three approaches for the same multi-domain defensive action that can be applied in such an alliance: 1) Counteract Everywhere, 2) Minimize Countermeasures, and 3) Minimize Propagation. First, we provide a formula to compute efficiency of a defense; then we use this formula to compute the efficiency of the approaches under various circumstances. Finally, we discuss how task execution order and timing influence defense efficiency. Our results show that the Minimize Propagation approach is the most efficient method when defending against the chosen attack.
Keywords: computer network security; multinetwork environments; multidomain defensive action; task execution order; timing influence defense efficiency; distributed attacks; collaborative security defence approach; minimize propagation approach; minimize countermeasure approach; counteract everywhere approach; Conferences; Cloud computing; Computer crime; Edge computing; Security; Defense Approaches; Multi-Domain Defense; Collaborative Defense; Defense Algorithms; Computer Networks

Fast and Accurate Audio Resampling for Acoustic Sensor Networks by Polyphase-Farrow Filters with FFT Realization - Schmalenstroeer, Joerg; Chinaev, Aleksej; Enzner, Gerald (Speech Communication; 13th ITG-Symposium)
Arbitrary sampling rate conversion has already received considerable attention in the past, but still lacks an equivalent representation of the effective time-dilation process in the block frequency domain. Good sampling rate converters in the time domain have been known, for instance, in terms of time-varying 'Sinc' or fixed 'Farrow' polynomial filters. The former can deliver nearly exact conversion at high complexity, while the latter has pronounced computational efficiency with limited accuracy. Only recently, it was shown that a composite 'polyphase Farrow' form with high resampling precision can be implemented with quasi-fixed filters that operate at the input sampling rate. We therefore propose to capitalize from that fixed-filter architecture in that we translate the polyphase-Farrow filters into an equivalent FFT-based overlap-save form. Experimental evaluation and comparison with other state-of-the art frequency-domain approaches then proves currently the best price-performance ratio of the proposed algorithm. It is thus an ideal candidate for the new framework of acoustic sensor networks that critically rests upon fast and accurate alignment of autonomous sampling processes.